PENGARUH KOMBINASI PENYUNTIKAN OVAPRIM DAN PROSTAGLANDIN F2 α (PGF2 α) TERHADAP DAYA RANGSANG OVULASI DAN KUALITAS TELUR IKAN MOTAN (Thynnicthys thynnoides Blkr) - Sukendi Sukendi; Ridwan Manda Putra; Yurisman Yurisman (Berkala Perikanan Terubuk, 2010)
The experiment were conducted to study the effect of ovaprim danprostaglandin F2α (PGF2α) combination on inducing ovulation and egg quality ofThynnicthys thynnoides Blkr. The experiment used five treatments as following :A1 = 50 % ovaprim + 50 % PGF2 α (0.35 ml/kg of body weight + 1500 μg/kg ofbody weight), A2 = 75 % ovaprim + 25 % PGF2 α (0.525 ml/kg of body weight +750 μg/kg of body weight), A3 = 25 % ovaprim + 75 % PGF2 α (0.175 ml/kg ofbody weight + 2250 μg/kg of body weight, A4 = 100 % ovaprim (0.7 ml/kg ofbody weight) and A5 = 100 % PGF2 α (3000 μg/kg of body weight). Thetreatments affected on inducing ovulation and egg quality. The best results wereabtimes from treatment A1 (0.35 ml/kg of body weight + 1500 μg/kg of bodyweight) with average values : latent period of 6.08 hours, number of ovulated eggswere 16308, egg diameter defference of 0.23 mm and gonad maturationdefference of 20 %.